How Russia’s war strengthens the West - Larsen, Henrik (Politica, 2023)
This article highlights three key areas of Western adaptation to Russia’s war against Ukraine with advice for how to optimize them going forward. First is the immediate strengthening of NATO’s conventional defense against Russia, whose sustainability will depend on European contributions, as the US increasingly will focus on Asia. Second is the preservation of joint resilience against both Russia and China, in which NATO should stick to the narrow military areas and the EU to the broader civilian areas. Third is the question of Ukraine as part of the West, where the former’s poor reform record and the latter’s unwillingness to intervene militarily on its behalf draw the realistic scenario of the country’s continued association.